2015
DOI: 10.1002/em.21952
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the mutagenic potential of Cr(VI) in the oral mucosa of Big Blue® transgenic F344 rats

Abstract: Exposure to high concentrations of hexavalent chromium [Cr(VI)] in drinking water was associated with an increased incidence of oral tumors in F344 rats in a 2-year cancer bioassay conducted by the National Toxicology Program. These tumors primarily occurred at 180 ppm Cr(VI) and appeared to originate from the gingival mucosa surrounding the upper molar teeth. To investigate whether these tumors could have resulted from a mutagenic mode of action (MOA), a transgenic mutation assay based on OECD Test Guideline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 46 publications
(81 reference statements)
5
15
0
Order By: Relevance
“…, Supporting Information Table SI). This finding is consistent with that observed in a subsequent study in which drinking water was used as vehicle control [Thompson et al, ]. In that study, the MF was 39.1 ± 7.5 × 10 −6 (19%) in gingiva/buccal tissues and 49.8 ± 17.8 × 10 −6 (36%) in gingiva/palate tissues.…”
Section: Resultssupporting
confidence: 91%
“…, Supporting Information Table SI). This finding is consistent with that observed in a subsequent study in which drinking water was used as vehicle control [Thompson et al, ]. In that study, the MF was 39.1 ± 7.5 × 10 −6 (19%) in gingiva/buccal tissues and 49.8 ± 17.8 × 10 −6 (36%) in gingiva/palate tissues.…”
Section: Resultssupporting
confidence: 91%
“…The general lack of transcriptional changes in the oral mucosa is entirely consistent with previous histopathology data indicating no non‐neoplastic or pre‐neoplastic changes in the oral mucosa of rats or mice [NTP, ; NTP, ; Thompson et al, ; Thompson et al, ]. Likewise, exposure to 180 ppm Cr(VI) did not increase cII transgene mutant frequency in TgF344 rats [Thompson et al, ]. To date, the only dose‐dependent changes in the oral mucosa in response to Cr(VI) were decreases in GSH and increases in GSSG levels in rats, which were not apparent in mice [Thompson et al, ; Thompson et al, ].…”
Section: Discussionsupporting
confidence: 86%
“…Using the OECD 28 + 3 exposure protocol (i.e., 28 days of exposure followed by necropsy on day 31), the oral mutagenic carcinogen 4‐nitroquinoline‐1‐oxide (4NQO) increased mutant frequency (MF) 20‐ to 50‐fold in the oral mucosa, but not in liver or bone marrow [Young et al, ]. A subsequent study from the same laboratory again found that 4NQO increased MF in the oral mucosa, whereas exposure to 180 ppm Cr(VI) did not increase MF in the oral mucosa of TgF344 rats [Thompson et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Toxicogenomic analyses indicate minimal, if any, gene expression changes in the oral mucosa of F344 rats or B6C3F1 mice exposed to ≤180 ppm Cr(VI) for 7 or 90 days (Thompson et al, 2016). Exposure to 180 ppm Cr(VI) for 28 days did not increase mutant frequency in oral tissue of Big Blue® F344 rats (Thompson, Young, et al, 2015). Taken together, these data indicate that Cr(VI) elicits minimal, if any, direct cellular responses in the oral mucosa of rats or mice.…”
Section: Resultsmentioning
confidence: 99%
“…To inform the MOA and risk assessment of oral Cr(VI) exposure, a series of studies were conducted beginning with an overall proposed MOA (Thompson, Haws, Harris, Gatto, & Proctor, 2011), and subsequent 90‐day toxicity studies (Thompson, Proctor, et al, 2011; Thompson et al, 2012), transcriptomic analyses (Kopec et al, 2012; Kopec, Thompson, Kim, Forgacs, & Zacharewski, 2012; Rager et al, 2017), genotoxicity studies (O'Brien et al, 2013; Thompson, Seiter, et al, 2015; Thompson, Wolf, et al, 2015; Thompson, Young, et al, 2015; Thompson et al, 2017), as well as ex vivo gastric reduction studies and pharmacokinetic modeling (De Flora et al, 2016; Kirman et al, 2012; Kirman et al, 2013; Kirman et al, 2016; Proctor et al, 2012). Other genotoxicity studies were conducted in response to early drafts of the NTP 2‐year cancer bioassay (De Flora et al, 2006; De Flora et al, 2008).…”
Section: Introductionmentioning
confidence: 99%